PERAN BRAND AWARENESS SEBAGAI MEDIASI PENGARUH IKLAN TELEVISI DAN BRAND AMBASSADOR TERHADAP REPURCHASE INTENTION PRODUK KECANTIKAN WARDAH (Studi Kasus Pada Mahasiswi Program Sarjana FEB Universitas Brawijaya Malang yang Menggunakan Produk Kecantikan Wardah) - Endang Sri Utami (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Advertising is very important in corporate marketing and is useful to convey a message to potential customers and loyal consumers. Companies can promote a product or service through printed and electronic media. Television electronic media can be interesting if there is a brand ambassador in the delivery of the message since it can create brand awareness on consumers and thus influence them to make purchasing decisions.This study aims to analyze whether television advertising and brand ambassador directly have a significant effect on brand awareness and indirectly have significant on repurchase intention. The population of this research is student of Faculty of Economics and Business of Brawijaya University who likes to put on make up. The sample of this research is 130 respondents obtained through purposive sampling method. The data of this research were path analyzed using path analysis with smartPLS.The results show that television advertising and brand ambassador of Wardah have a direct and significant influence on brand awareness and indirect influence on repurchase intention. Furthermore, brand awareness is defined as partial mediation.Keyword: Television Advertising, Brand Ambassador, Brand Awareness, Repurchase Intention